2002
DOI: 10.1021/jf010716t
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimutagenic Properties of Aqueous Extract of Date Fruit (Phoenix dactyliferaL. Arecaceae)

Abstract: Fruits of the date palm (Phoenix dactylifera L. Arecaceae) are very commonly consumed in many parts of the world and are a vital component of the diet in most of the Arabian countries. This preliminary study documents for the first time its antioxidant and antimutagenic properties in vitro. There was a dose-dependent inhibition of superoxide and hydroxyl radicals by an aqueous extract of date fruit. The amount of fresh extract required to scavenge 50% of superoxide radicals was equivalent to 0.8 mg/mL of date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
248
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(264 citation statements)
references
References 35 publications
13
248
0
3
Order By: Relevance
“…Soaking strawberry in salicylic acid at 2 mM was found to be effectively to increase total antioxidant potential, ascorbic acid content, total soluble solids and prevented fungal contaminations (Asghari and Aghdam 2010). It is established that the AC of dates was due mainly to the presence of water-soluble compounds with potent free radical-scavenging effects, including the phenolic compounds (mainly cinnamic acids) and flavonoids (flavones, flavonols and flavanones) (Wang et al 1996;Connor et al 2002;Vayalil 2002;Guo et al 2003;Mansouri et al 2005;Biglari et al 2008). Significant correlation between AC and TP content in date palm fruits has been established by many investigators (Allaith 2008;Biglari et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Soaking strawberry in salicylic acid at 2 mM was found to be effectively to increase total antioxidant potential, ascorbic acid content, total soluble solids and prevented fungal contaminations (Asghari and Aghdam 2010). It is established that the AC of dates was due mainly to the presence of water-soluble compounds with potent free radical-scavenging effects, including the phenolic compounds (mainly cinnamic acids) and flavonoids (flavones, flavonols and flavanones) (Wang et al 1996;Connor et al 2002;Vayalil 2002;Guo et al 2003;Mansouri et al 2005;Biglari et al 2008). Significant correlation between AC and TP content in date palm fruits has been established by many investigators (Allaith 2008;Biglari et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…6 Dates fruit are a good source of sugars, fibers, and minerals, 7 exhibiting many beneficial health effects such as being antioxidant, 8 antimutagenic, 9 antibacterial, 10 antitumoral, 11 and antifungal. 12 Recently, Zangiabadi et al 13 demonstrated that dates fruit extract treatment was effective in preventing diabetic deterioration and in improving pathological parameters of diabetic neuropathy.…”
Section: Introduction Cmentioning
confidence: 99%
“…Dates are rich in carbohydrates, tannins and minerals; they exhibit antioxidant, antimutagenic and freeradical-scavenging activity (Vayalil 2002). Dates from this region are generally harvested at immature stage due to the on set of monsoon.…”
Section: Introductionmentioning
confidence: 99%